Analisis Strategi Pemasaran Merek HAUS! Indonesia pada Industri Minuman Kekinian di Era Digital - Andi Suhandi; Azmi Muhammad Habibie; Sri Wahyuningsih (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2026)
This study analyzes the success strategies of the contemporary beverage brand HAUS! Indonesia in dominating the middle class segment. The study focuses on product innovation, price and value perception, distribution, branding, as well as consumer loyalty and purchasing decisions. A descriptive qualitative approach through literature study was used to examine relevant theories and empirical findings. The results of the study show that adaptive product innovation, economical pricing strategies, distribution integrated with digital channels, and strong branding and social media engagement play an important role in building consumer loyalty. HAUS! has successfully maintained its relevance as a sustainable brand amid competition in the ready-to-drink beverage market.